Warm-up is an efficient strategy to prevent diurnal variation of short-term maximal performance in young basketball players - Zelenović, Milan; Kontro, Titta; Čaušević, Denis; Bjelica, Bojan; Aksović, Nikola; Milanović, Zoran (Chronobiology international, 2024)
The objectives of this study were to investigate: 1) whether there were morning-to-evening differences in short-term maximal performance and 2) the impact of prolonged and specific warm-up on short-term maximal performance diurnal variations in young basketball players. Fifteen basketball players of both sexes (Male = 8; Female = 7; age: 14.4 ± 0.46 yr; weight: 64.7 ± 7.1 kg; height: 175.2 ± 6.6 cm; BMI: 21.1 ± 1.9 kg/m2) completed the following short-term maximal performance tests: CMJ with and without arm swing, Lane Agility Drill, Zig-Zag agility test with and without the ball, Sprint 20 m with and without the ball with the passage at 5 and 10 m. All tests were performed after the 15-min standard warm-up procedure (with static stretching) and/or 25-min specific warm-up (with prolonged running and dynamic stretching) in the morning and evening. Vertical jumping tests and all change-of-direction speed tests (with and without a ball) with superior responses were achieved in the evening after standard warm-up among all participants (p < 0.05). In contrast, superior short-term maximal performance was observed in the morning after prolonged and specific warm-up protocol (p < 0.05). It was concluded that specific and prolonged warm-up protocols are suitable strategy to prevent diurnal variation in short-term maximal performance in young basketball players.
Keywords: Female; physical performance; ženské pohlaví; Muscle Stretching Exercises; Adolescent; basketbal; běh; lidé; Athletic Performance; team sport; Circadian Rhythm; cirkadiánní rytmus; Running; Basketball; Male; strečink; sportovní výkon; mužské pohlaví; diurnal effect; mladiství; Humans